2000
DOI: 10.1590/s0103-50532000000300016
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)-dissolved in ionic liquids: a recyclable catalytic system for the selective biphasic hydrogenation of dienes to monoenes

Abstract: Bis-acetilacetonato de paládio dissolvido no líquido iônico tetrafluoroborato de 1-n-butil-3-metilimidazólio catalisa de forma seletiva a hidrogenação de dienos conjugados e não-conjugados (funcionalizados ou não) às suas respectivas mono-olefinas. O sistema não requer o uso de cosolventes orgânicos, sendo os produtos da reação separados por simples decantação ou destilação. A fase iônica pode ser reutilizada até 15 vezes sem perdas significativas na sua atividade catalítica e seletividade.Palladium acetylacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 8 publications
(12 reference statements)
0
39
0
1
Order By: Relevance
“…Work by Dupont and co-workers [11] using Pd(acac) 2 dissolved in the ionic liquid 1-n-butyl-3-methylimidazolium tetrafluoroborate (BMIM.BF 4 ) resulted in the hydrogenation of simple and functionalized dienes to their corresponding monoolefins at 50 8C and 5 -20 atm in selectivities ranging from 93 to 100%. Kaneda and co-workers demonstrated that the dendrimer-bound palladium complex of phosphonated poly(propyleneimine) can selectively hydrogenate conjugated cyclic dienes to monoolefins.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Dupont and co-workers [11] using Pd(acac) 2 dissolved in the ionic liquid 1-n-butyl-3-methylimidazolium tetrafluoroborate (BMIM.BF 4 ) resulted in the hydrogenation of simple and functionalized dienes to their corresponding monoolefins at 50 8C and 5 -20 atm in selectivities ranging from 93 to 100%. Kaneda and co-workers demonstrated that the dendrimer-bound palladium complex of phosphonated poly(propyleneimine) can selectively hydrogenate conjugated cyclic dienes to monoolefins.…”
Section: Introductionmentioning
confidence: 99%
“…These results contrast with those obtained using [Pd(acac) 2 ] as catalyst precursor, where no changes on selectivity was observed by changing the ionic liquid. 18 As shown in Table 3 other transition metal acetylacetonates complexes are also able to hydrogenate 1,3-butadiene under relatively mild reaction conditions. As observed in the hydrogenation reactions with [Co(acac) 2 ], the separation of the products from the reaction mixture can be performed by simple decantation and the recovered ionic catalyst solution can be reused without any significant changes in activity or selectivity.…”
mentioning
confidence: 97%
“…The Pd-catalyzed hydrogenation of dienes to mono-hydrogenated olefins was effectively obtained in ILs. 178 The 6 ] was derived from a common phase transfer catalyst Aliquat 336. It was observed that the selectivity profiles of citral hydrogenation can be efficiently influenced not only by varying the transition metal species in line with classical catalysis and the experimental conditions (temperature, pressure), but also by the choice of the ionic liquid in which the transition metal species is dissolved.…”
Section: Hydrogenationmentioning
confidence: 99%